2021
DOI: 10.3390/math9161997
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Interval Reliability for Discrete-Time Homogeneous Semi-Markov Repairable Systems

Abstract: In this paper, a new reliability measure, named sequential interval reliability, is introduced for homogeneous semi-Markov repairable systems in discrete time. This measure is the probability that the system is working in a given sequence of non-overlapping time intervals. Many reliability measures are particular cases of this new reliability measure that we propose; this is the case for the interval reliability, the reliability function and the availability function. A recurrent-type formula is established fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…One of the most important 3-state semi-Markov models is the generalized object reliability model developed by Grabski [13], validated with assumed parameter values, without specified references to technical data. In the course of the research, the authors developed original 3-state models applicable to specific objects and systems, e.g., four types of repairable systems [8], single-use systems [9], special vehicles [5], lithium-ion batteries [55] and repairable systems [3]. Mengistu et al [28] identified a five-state phase space of the semi-Markov model for volunteer cloud systems and Wu et al [56] for power stations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most important 3-state semi-Markov models is the generalized object reliability model developed by Grabski [13], validated with assumed parameter values, without specified references to technical data. In the course of the research, the authors developed original 3-state models applicable to specific objects and systems, e.g., four types of repairable systems [8], single-use systems [9], special vehicles [5], lithium-ion batteries [55] and repairable systems [3]. Mengistu et al [28] identified a five-state phase space of the semi-Markov model for volunteer cloud systems and Wu et al [56] for power stations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Technical objects (general) [13] Four types of repairable systems [8] Single-use system [9] Special vehicles [5] Lithium-ion batteries [55] Repairable systems [3] 5-state model Volunteer cloud systems [28] Power station [56] 4-and 6-state models Repairable systems under alternative environments [50] 7-state model Modular multilevel converter system [57] 9-state model Two machines operating in parallel [4]…”
Section: -State Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we study a specific reliability indicator of discrete-time semi-Markov systems called sequential interval reliability (SIR) which has been recently introduced in [1].…”
Section: Introductionmentioning
confidence: 99%
“…(ii3) Sequential Interval Reliability for Discrete-Time Homogeneous Semi-Markov Repairable Systems, by Barbu, V.S., D'Amico, G. Gkelsinis, T. [19]. This is another paper of the special issue concerned with reliability indicators; however, this one is dedicated to semi-Markov systems.…”
mentioning
confidence: 99%